A Case for Multisite Second Language Acquisition Research: Challenges, Risks, and Rewards. Issue 1 (30th November 2020) - Moranski, Kara; Ziegler, Nicole
Abstract: Multisite research (MSR) offers the key advantages of greater statistical power and external validity via larger and more diverse participant pools. In second language acquisition (SLA) research, recent developments in meta‐analysis have created a robust foundation for MSR. Although logistical and financial obstacles can complicate expansion beyond a single site, we show that MSR's benefits can justify the investment of resources. We begin by outlining how developments in meta‐analytic research, replication, and access to data and materials have created an especially opportune moment for MSR. Next, we discuss the methodology for a classroom study on metacognitive instruction as an illustrative case, outlining the major elements of its design and implementation. Finally, we review how four issues critical to MSRs (funding, compliance, logistics, and analysis) were addressed in our example study, including a discussion on multilevel modeling. We conclude with a discussion of how the field can build upon existing research to advance multisite work. Abstract :